2018
DOI: 10.1111/boc.201800060
|View full text |Cite
|
Sign up to set email alerts
|

Rsph9 is critical for ciliary radial spoke assembly and central pair microtubule stability

Abstract: Background Information In the “9+2”‐type motile cilia, radial spokes (RSs) protruded from the nine peripheral microtubule doublets surround and interact with the central pair (CP) apparatus to regulate ciliary beat. RSPH9 is the human homologue of the essential protozoan RS head protein Rsp9. Its mutations in human primary ciliary dyskinesia patients, however, cause CP loss in a small portion of airway cilia without affecting the ciliary localization of other head proteins. Results We characterized mouse Rsph9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…Our video microscopy results showed that the movement of beating cilia bundles is characterized by lower amplitude and disorderly rotation beating pattern instead of orderly planar beating pattern in subventricular zone en-face of Rsph9 −/− mice. Liu et al reported that knockdown of RSPH9 by RNAi in mouse ependymal cells, which differentiated from radial glia ex vivo, resulted in a near complete CP loss 26 ; however, our results showed that there were no defects with CP in Rsph9 −/− ependymal motile cilia in vivo, and few exhibited various ultrastructure disorganizations. This may be due to the truncated RSPH9, which may still support the central pair formation, or the differences between in vivo and in vitro experiments.…”
Section: Discussioncontrasting
confidence: 81%
“…Our video microscopy results showed that the movement of beating cilia bundles is characterized by lower amplitude and disorderly rotation beating pattern instead of orderly planar beating pattern in subventricular zone en-face of Rsph9 −/− mice. Liu et al reported that knockdown of RSPH9 by RNAi in mouse ependymal cells, which differentiated from radial glia ex vivo, resulted in a near complete CP loss 26 ; however, our results showed that there were no defects with CP in Rsph9 −/− ependymal motile cilia in vivo, and few exhibited various ultrastructure disorganizations. This may be due to the truncated RSPH9, which may still support the central pair formation, or the differences between in vivo and in vitro experiments.…”
Section: Discussioncontrasting
confidence: 81%
“…Unless otherwise 393 indicated, the culture medium was Dulbecco's Modified Eagle's medium (DMEM) 394 supplemented with 10% fetal bovine serum (Biochrom, Cambridge, UK), 0.3 mg/ml 395 glutamine (Sigma), 100 U/ml penicillin (Invitrogen), and 100 U/ml streptomycin 396 (Invitrogen). Multiciliated mouse ependymal cells were obtained and cultured as 397 described (Zhu et al, 2019). Briefly, the telencephalon taken from the P0 C57BL/6J 398 mice were digested and spread onto laminin coated flasks.…”
Section: Cell Culture and Immunofluorescent 392mentioning
confidence: 99%
“…We first examined whether all the mouse homologous RS head proteins (Rsph1, 4a, 6a, 96 9 and 10b) and RSP3 (Rsph3b) localize in the axoneme of motile cilia in multiciliated 97 mouse ependymal cells (mEPCs) (Delgehyr et al, 2015;Zhu et al, 2019). We found 98 that all these subunits except Rsph6a can be localized in the cilia of mEPCs ( Figure 99 1A).…”
mentioning
confidence: 99%
“…We observed that the ciliary localizations of multiple CP proteins, including CP MTs-associated Spef1, C2 MT-associated Hydin, C1 MT-associated Spag6, and C1-C2 bridge-associated Spag16 (Fig. 2a, S3) 22,35,44 , were abolished or markedly reduced in Wdr47 -/-mEPCs, whereas Rsph4a, a radial spoke component 45,46 , was not affected ( Fig. 2b; Fig.…”
Section: Wdr47 Is Critical For Both Ciliary Localization Of Cp Proteimentioning
confidence: 92%